2013
DOI: 10.1093/cvr/cvt201
|View full text |Cite
|
Sign up to set email alerts
|

NO-dependent CaMKII activation during β-adrenergic stimulation of cardiac muscle

Abstract: β-AR stimulation of cardiomyocytes may activate CaMKII by a novel direct pathway involving NO, without requiring Ca(2+) transients. This crosstalk between two established signalling pathways may contribute to arrhythmogenic diastolic Ca(2+) release and Ca(2+) waves during adrenergic stress, particularly in combination with cardiac diseases. In addition, NO-dependent activation of CaMKII is likely to have repercussions in many cellular signalling systems and cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
93
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 53 publications
4
93
1
2
Order By: Relevance
“…However, this rather small effect may have been caused by ONOO Ϫ -mediated oxidation (an effect that was ruled out in our experiments on the CaMKII␣ isoform). Indeed, in this case, the NO effect was no larger than the effect of oxidation (46), and the CaMKIIó isoform does not have a Cys residue at the position homologous to Cys-280 in CaMKII␣ (and the nitrosylation effect on CaMKII␣ autonomy demonstrated here was sensitive not only to mutation of the Cys-289 that is conserved among the isoforms, but also to mutation of the unique Cys-280).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, this rather small effect may have been caused by ONOO Ϫ -mediated oxidation (an effect that was ruled out in our experiments on the CaMKII␣ isoform). Indeed, in this case, the NO effect was no larger than the effect of oxidation (46), and the CaMKIIó isoform does not have a Cys residue at the position homologous to Cys-280 in CaMKII␣ (and the nitrosylation effect on CaMKII␣ autonomy demonstrated here was sensitive not only to mutation of the Cys-289 that is conserved among the isoforms, but also to mutation of the unique Cys-280).…”
Section: Discussionmentioning
confidence: 72%
“…However, in this case, CaMKII activation by NO did not appear to be through direct S-nitrosylation, as CaMKII activation (and the downstream functions) was instead dependent on PKG (47), which is activated by cGMP after NO-induced guanylyl cyclase activation (17)(18)(19). Notably, however, one of these studies showed that NO donors did also cause a direct 2.5-fold increase of CaMKIIó activity over baseline (46). However, this rather small effect may have been caused by ONOO Ϫ -mediated oxidation (an effect that was ruled out in our experiments on the CaMKII␣ isoform).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, CaMKII␦ activity is enhanced by NO donors (14), there is evidence that myocyte CaMKII can be nitrosylated (11,12), and several S-nitrosylation sites have been predicted by consensus modeling. Therefore, CaMKII␦ may be directly modified by NO (12).…”
mentioning
confidence: 99%
“…For example, ␤-adrenergic stimulation activates CaMKII␦ in part through an NO synthase-dependent pathway (11), which increases the sarcoplasmic reticulum Ca 2ϩ leak via ryanodine receptors (11,12,13). Moreover, CaMKII␦ activity is enhanced by NO donors (14), there is evidence that myocyte CaMKII can be nitrosylated (11,12), and several S-nitrosylation sites have been predicted by consensus modeling. Therefore, CaMKII␦ may be directly modified by NO (12).…”
mentioning
confidence: 99%